The Role Of Product Innovation In Consumer Purchasing Decisions - Debiyanti Kune; Wahyudin Rahman (International Forum of Researchers and Lecturers, 2022)
The purpose of this study is to determine how product innovation, brand image, and digital strategy affect the purchasing decisions of Palu consumers regarding Indomilk milk. The employed research methodology is quantitative in nature, incorporating both primary and secondary sources of data. The study's population comprises Indomilk milk consumers residing in Palu, the exact number of whom has not been determined. Due to the unknown quantity of the population, the number of respondents for this survey was calculated using the Paul Leedy formula and came to 81. The data for this study was gathered through the distribution of a questionnaire to the sample of respondents. This study employed various data analysis techniques, including instrumental tests, tests for double linear regression, t tests, F tests, and determination coefficient tests. On the basis of this study's data analysis, it is possible to conclude that product innovation, brand image, and digital strategy significantly impact the purchasing decisions of Palu consumers regarding Indomilk.